2000
DOI: 10.1097/00003246-200006000-00030
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin promotes adhesion of human erythrocytes to human vascular endothelial cells under conditions of flow

Abstract: Exposure of human erythrocytes and human venous vascular endothelial cells to an inflammatory stimulus such as endotoxin promotes a dose-dependent adhesion of erythrocytes to endothelium in a dynamic environment. These adhesive erythrocyte-endothelium interactions can be produced by exposure of either red blood cells or endothelial cells to endotoxin, with a higher degree of adhesion after activation of the endothelial cell component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 25 publications
2
24
1
3
Order By: Relevance
“…The LPS-induced fall in RBC counts can probably be attributed to enhanced degradation (due to decreased deformability and increased osmotic fragility), consumption into microaggregates and reduced production (under bone marrow suppression of erythropoietin levels). 56,57 The rapid leukocyte decrease is likely due to tissue migration. 5,58 Together, these observations support the notion that AChE-R plays an active role in the proliferation of hematopoietic progenitors, especially Mks, without compromising their ability to differentiate into the various hematopoietic lineages.…”
mentioning
confidence: 99%
“…The LPS-induced fall in RBC counts can probably be attributed to enhanced degradation (due to decreased deformability and increased osmotic fragility), consumption into microaggregates and reduced production (under bone marrow suppression of erythropoietin levels). 56,57 The rapid leukocyte decrease is likely due to tissue migration. 5,58 Together, these observations support the notion that AChE-R plays an active role in the proliferation of hematopoietic progenitors, especially Mks, without compromising their ability to differentiate into the various hematopoietic lineages.…”
mentioning
confidence: 99%
“…Although not extensively investigated, there is some evidence for this phenomenon. Incubation of both endothelial cells and RBCs with endotoxin increased adherence of RBCs to endothelial monolayers [105]. This effect was also observed after stimulation with TNF- [106].…”
Section: Reduced Deformabilitymentioning
confidence: 72%
“…In a previous investigation we observed that ETX promotes adhesion of RBCs to venous endothelial cells at continuous flow [3]. However, shear forces are sometimes inconsistent and shear forces lower than those occurring with physiological venous flow are observed in near stasis conditions, such as might be found during the process of acute inflammation [32].…”
Section: Discussionmentioning
confidence: 88%
“…Reductions in the perfused capillary density, increased intermittent flow or flow stasis, and alterations in red blood cell velocity relative to normal subjects have been found after exposure to ETX or peritonitisinduced sepsis [9,11,12]. In a previous investigation we demonstrated that ETX increases RBC adhesion to endothelium in a dynamic environment generated by constant flow [3]. The accumulated evidence suggests that the various microcirculatory blood flow pattern and shear forces particularly those prevailing in splanchnic organs during systemic inflammation affect RBC-endothelial cell interactions.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation